(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The article presents the modern problem of the Aral Sea, which needs to be solved urgently in the international plan, indicates the possibility of smoothing the negative consequences of the Aral Sea by forest plantations on the drained bottom of the sea. The analysis of the scatter method is given. The design of the existing SLP-M seeder used in forest nurseries is analyzed, the disadvantages of which are the complexity of the design and the impossibility of its use for sowing seeds on large areas with wide rows and large intervals between them. Considering the above, a single-row seeder has been developed for sowing saxaul seeds. It consists of a frame, a seed box, two support-drive wheels. A seeding coil is installed at the bottom of the seed box. A lever is installed on the axis of the two support-drive wheels, which rotates the seeding coil once at each rotation of the wheels, thereby ensuring sowing seeds with an interval of length equal to the circumference of the support wheels. It is known that the problem of the Aral Sea in the international plan is among the priority tasks that need to be solved urgently, the consequences of which are continental in nature. Smoothing out the negative consequences of the Aral Sea can be achieved only by means of forest plantations on the drained bottom of the sea. Desert plants like kandym, saxaul and cherkez are used for this. Saxaul plantation fix the sands, reduce wind-borne sediments, improve water infiltration into the soil and improve its structure.